Pharmacokinetics and Bioavailability Comparison of two oral Tablet Formulations of Escitalopram 20 mg: A Single-Dose, Open-Label, Two-Period Crossover Study in Healthy Indian Adult Subjects: Bio-equivalence of Escitalopram in Healthy Indian subjects - Kotakonda Harish Kaushik; S.Vijay Kumar; Y. Narasimha Reddy; M.Nagulu (Iranian Journal of Pharmaceutical Sciences, 2014)
This study was undertaken to assess bioequivalence between test and reference formulations of escitalopram oxalate 20 mg in healthy Indian male subjects. This single-dose, randomized, open-label, 2-period crossover study was carried out in 12 Healthy Indian Male volunteers aged 18 to 55 years under fasting conditions with a wash out of 14 days. The subjects were randomly assigned to receive the test formulation followed by the reference formulation, and then vice versa. Blood samples were collected for up to 156 h postdose. Quantification was carried out using a validated LC-MS/MS method. Maximum plasma concentrations Cmax of 26.386 ± 5.54 ng/mL (test) and 24.430 ± 3.52 ng/mL (reference) were achieved. Areas under the plasma concentration-time curve AUC0-inf of 854.241 ± 91.22 ng. hr/mL (test) and 825.135 ± 1.37 ng. hr/mL (reference), AUC0-t of 848.766 ± 93.26 ng. hr/mL (test), 819.504 ± 1.91 ng. hr/mL (reference) were calculated. The median Tmax was 4.00 hr for test and reference formulation, respectively. Plasma elimination half-lives T1/2 of 19.26 ± 5.95 hr (test), 20.94 ± 2.88 hr (reference) were determined. Both formulations were well tolerated. The 90% confidence intervals obtained by analysis of variance were 94.49-120.68% for Cmax and 98.22-108.18% for AUC0-t which were within the predefined regulatory acceptance limit of 80.00-125.00%.